Measurement of four-jet differential cross sections in $\sqrt{s}=8$ TeV proton-proton collisions using the ATLAS detector - ATLAS collaboration (2857 authors) (2015)
Differential cross sections for the production of at least four jets have been measured in proton-proton collisions at $ \sqrt{s}=8 $ TeV at the Large Hadron Collider using the ATLAS detector. Events are selected if the four anti-k$_{t}$ R = 0.4 jets with the largest transverse momentum (p$_{T}$) within the rapidity range |y| < 2.8 are well separated (ΔR$_{4j}^{min}$  > 0.65), all have p$_{T}$ > 64 GeV, and include at least one jet with p$_{T}$ > 100 GeV. The dataset corresponds to an integrated luminosity of 20.3 fb$^{−}^{1}$ . The cross sections, corrected for detector effects, are compared to leading-order and next-to-leading-order calculations as a function of the jet momenta, invariant masses, minimum and maximum opening angles and other kinematic variables.